PEMANFAATAN APLIKASI QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BAGI SISWA TINGKAT SEKOLAH DASAR - Trisyana, Nike; Romli Triputra , Dedi; Tri Setiyoko, Didik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore in depth how the Quizizz application can be optimally utilized by teachers and students at the elementary school level. The main focus is on identifying best practices in the use of Quizizz to effectively support the achievement of learning objectives. This research employs a qualitative approach using the literature study method (library research), which is intended to examine and analyze various scholarly sources and previous research related to the use of the Quizizz application. The utilization of Quizizz in elementary schools can be optimized through several wise strategies, such as designing quizzes that match students' skill levels to maintain relevance, using the self-correction feature to enhance understanding, and managing time effectively to prevent students from rushing. Additionally, to address issues related to unstable internet connections, schools need to ensure adequate infrastructure and provide supervision to prevent students from seeking answers from external sources.